2015
DOI: 10.1523/jneurosci.2127-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Protein Tyrosine Phosphatase Receptor Type Z by Pleiotrophin Promotes Remyelination through Activation of Differentiation of Oligodendrocyte Precursor Cells

Abstract: Multiple sclerosis (MS) is a progressive neurological disorder associated with myelin destruction and neurodegeneration. Oligodendrocyte precursor cells (OPCs) present in demyelinated lesions gradually fail to differentiate properly, so remyelination becomes incomplete. Protein tyrosine phosphatase receptor type Z (PTPRZ), one of the most abundant protein tyrosine phosphatases expressed in OPCs, is known to suppress oligodendrocyte differentiation and maintain their precursor cell stage. In the present study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

11
93
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(104 citation statements)
references
References 42 publications
11
93
0
Order By: Relevance
“…PTPRZ dephosphorylates p190 RhoGAP, thereby acting as a counterpart of FYN (11,12). The amounts of myelin basic protein (MBP) and myelinated axons in the brain at postnatal day 10, when myelination occurs, are significantly higher in Ptprz-deficient mice than in wildtype animals, indicating a suppressive role for PTPRZ in oligodendrocyte differentiation (11).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…PTPRZ dephosphorylates p190 RhoGAP, thereby acting as a counterpart of FYN (11,12). The amounts of myelin basic protein (MBP) and myelinated axons in the brain at postnatal day 10, when myelination occurs, are significantly higher in Ptprz-deficient mice than in wildtype animals, indicating a suppressive role for PTPRZ in oligodendrocyte differentiation (11).…”
mentioning
confidence: 99%
“…PTN has been shown to inactivate the intracellular catalytic activity of PTPRZ-B by inducing molecular oligomerization in baby hamster kidney (BHK)-21 cells (22). We recently demonstrated that PTN enhanced thyroid hormone-induced OPC differentiation in a primary culture of glial cells from wild-type mice, but not Ptprzdeficient mice, indicating that its effects are mediated by PTPRZ (12,25). We established the oligodendrocyte-lineage cell line, OL1, from the p53-knock-out mouse brain (12).…”
mentioning
confidence: 99%
See 3 more Smart Citations